Weight status and bullying behaviors among Chinese school-aged children. (February 2016) - Liu, Xiaoqun; Chen, Gui; Yan, Junxia; Luo, Jiayou
Abstract: This study was to examine the relationship between measured weight status and three experiences as victims, bullies and bully-victims. The participants were 10, 587 Chinese school-aged students (girls: 5, 527, boys: 5, 060) who ranged in age from 7 to 18 years old. Height and weight were measured. Bullying behavior was obtained by one-to-one interview in 7–10 years older students and group-administered surveys in 11–18 years older students. The results showed that, obese girls were more likely to be victimized (OR = 1.73, CI: 1.16–2.59) compared to normal students. For boys, obesity was not associated with victimization, but obese boys (OR = 1.45, CI: 1.04–2.03), especially 7–13 years old boys (OR = 1.98, CI: 1.35–2.90) were more likely to bully others; obese boys also were more likely to be victim/bullies (OR = 1.67, CI: 1.05–2.64). Weight victimization in Chinese school-aged children is not as common as in the west countries, but obese girls clearly realize more victimization, and obese younger boys show obvious aggression. Related departments should provide specific intervention for school bullying according students' weight status, age and gender.